Case report on a retroperitoneal sarcoma encasing left common iliac vein in a 65 years old elderly woman - Godhani, Meet Rajeshbhai; Kandoi, Nilay Kaushik (International Surgery Journal, 2023)
A 65 years old married female patient presented to us with chief complaints of dull aching back pain, radiating upto left thigh since 1 year. MRI pelvis revealed a large heterogeneous solid lesion in retroperitoneum in the paravertebral region. Intraoperatively, the mass was encasing the Left Common Iliac Vein which was lighted. Since, the presentation was chronic the venous collaterals in the left lower limb was already formed and there was no need for venous reconstruction. The Left lower limb did not suffer any complications and the patient was discharged on 10th post operative day. When there is chronic obstruction of Common Iliac Vein, usually venous collaterals develops and the lower limb can be salvaged without venous reconstruction.